Assessing corporate social responsibility in terms of its impact on sustainable community development : Anglo American PLC programmes as case study - Marais, Anel (Stellenbosch : University of Stellenbosch, 2010)
Thesis in partial fulfillment of the requirement for the degree of Master for Philosophy in Community and Development at the University of Stellenbosch